Experimenting with the New European Bauhaus Values and Principles in Urban Transformation - Deserti, Alessandro; Puerari, Emma (SpringerBriefs in applied sciences and technology, 2025)
This open access book offers valuable insights into experimenting with New European Bauhaus values and principles in urban transformation, drawing on contributions from key players such as local activists, action researchers, municipalities, developers and artists. It highlights lessons learned from the lighthouse project “Desire - Designing the Irresistible Circular Society", weaving a narrative of transformative change. The book emphasizes innovative strategies, citizen engagement, and transdisciplinary approaches in shaping urban environments. The journey begins with an in-depth exploration of the Desire project, providing a nuanced understanding of the broader context of its experiments and research activities. This foundation leads to an examination of diverse approaches to achieving sustainable, inclusive, and aesthetically enriching urban transformations. Readers are guided through the complexities of urban change, gaining a holistic understanding of how urban transformation and an irresistible circular society can be cultivated and sustained within the dynamic landscape of European cities. Additionally, the book presents findings from an EU lighthouse project, showcasing how urban transformation sites evolve by integrating lessons that could inform future policy, research, and further advancements within the New European Bauhaus initiative.